ICT, Innovation and Business Performance in Services: Evidence for Germany and the Netherlands - Henry van der Wiel; George van Leeuwen; Thomas Hempell (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
Using panel data for German and Dutch firms from the services sector, this paper analyses the importance of ICT capital deepening and innovation for productivity. We employ a model that takes into account that innovation and ICT use may be complementary. The results show that the contribution of ICT capital deepening is raised when firms combine ICT use and technological innovations on a more permanent basis. Moreover, the joint impact of ICT use and permanent technological innovation on productivity appears to be of the same order of magnitude in the two countries. However, the direct impacts of innovation on multi-factor productivity seems to be more robust for Germany than for the Netherlands.
Keywords: L80; D24; C23; O32; 330; Productivity; Information and Communication Technologies; Innovation; Services; Panel Data; Dienstleistungssektor; Informationstechnik; Computergesttztes Verfahren; Innovation; Produktivit t; Schtzung; Deutschland; Niederlande